Research on equivalent height compensation measurement method of UHF partial dispenser based on GTEM cell - Weiwei Zhang; Dongdong Xu; Wei Zhou; Yuxin Yun; Nan Wang (Energy Reports, 2020)
Based on the GTEM chamber for the equivalent height detection method of UHF partial discharge tester, this paper simulates the electric field at the top of the GTEM window. The results show that the electric field strength changes significantly along the position of the top fenestration axis. This change will have a non-negligible effect on the accuracy of the UHF partial discharge equivalent height measurement. In this way, an equivalent height compensation method for the UHF partial discharge tester is proposed. The method compensates for the electric field of the reference sensor position by using the electric field of the measured sensor position as a standard. Through the comparison before and after compensation, the method can effectively improve the accuracy of the equivalent height measurement of the UHF partial discharge tester.
Keywords: 330; Compensation amount; Effective height; GTEM cell; Partial discharge (PD); Ultra high frequency (UHF)